Case report: Frontal nasal osteoma with intracranial and dural invasion - Bretones , Victor Hugo; Vasconcelos, Jessica Blum de; Astolfo, Helena Blaya Fernandes; Outi, Hayani Yuri Ferreira; Malaspina, Iago Aum; Filho , Wilson Bretones; Ribeiro , Paulo Ronaldo Jube; Bassi , Samuel Gasperine (Seven Editora, 2023)
In this clinical case, a 21-year-old young woman with no family history of neurological diseases and no prior comorbidities sought medical attention due to persistent and progressive frontal headache, relieved with analgesics. Ophthalmological examinations did not reveal visual abnormalities. During the same period, the patient had an episode of dengue, characterized by rhinorrhea upon physical exertion. With the persistence of symptoms, the patient consulted a neurologist in December 2021 and underwent a computed tomography (CT) scan. The results showed an expansive lesion with bony density in the left frontal paranasal sinus. Histological analysis confirmed it was an Osteoid Osteoma. The diagnosis was of a fronto-nasal osteoma with intracranial and dural invasion. This rare condition can cause symptoms such as headache and nasal problems due to intracranial compression. Treatment typically involves surgery for osteoma removal and relief of intracranial compression. In summary, this case highlights the importance of accurate diagnosis of fronto-nasal osteomas, especially when they cause significant symptoms such as headache and intracranial compression. Surgical treatment may be necessary to improve the quality of life and alleviate symptoms of this rare but potentially debilitating condition. The provided references are additional resources for healthcare professionals dealing with similar cases. DOI:https://doi.org/10.56238/interdiinovationscrese-045